The Effectiveness of Bi Al-Kitabah Da'wah through the Media of Nurul Jadid Islamic Boarding School Newspaper: The Effectiveness of Bi Al-Kitabah Da'wah through the Media of Nurul Jadid Islamic Boarding School Newspaper - Ina, Septia Qorri 'Aina; Romadlany, Zakiyah (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
ABSTRACT This article discusses da'wah through print media (Bi Al-Kitabah). This paper aims to determine the effectiveness of spreading da'wah through print media, namely newspapers. In Islamic boarding schools, newspapers become an alternative medium for students to channel their thoughts and share knowledge. Being in the Pesantren environment does not close the boundaries for students in developing their insights. The development of technology today requires the younger generation to become an innovative and highly intellectual generation. Print media must now follow the flow of the times to maintain the existence of the media, one of which is by maintaining the actuality of writing. In the Nurul Jadid Paiton Islamic boarding school in Probolinggo – especially in the Qur'an Education Center of Nurul Jadid Islamic Boarding School, print media is the main media that is efficient and effective in disseminating information and knowledge for readers. In this descriptive qualitative research, researchers use data collection techniques through interviews, observations, and documentation from both offline and online sources. Based on the analysis of the collected data, it can be concluded that the use of print media in the form of newspapers in Islamic boarding schools can have a good impact on the development of knowledge, productivity of written works, and the effectiveness of spreading da'wah. Keywords: Effectiveness, Da'wah Bi al-Kitabah, Print Media ABSTRAK Artikel ini membahas dakwah melalui media cetak (Bi Al-Kitabah). Tulisan ini bertujuan untuk mengetahui efektivitas penyebaran dakwah melalui media cetak, yaitu surat kabar. Di pesantren, koran menjadi media alternatif bagi santri untuk menyalurkan pikiran dan berbagi ilmu. Berada di lingkungan Pesantren tidak menutup batasan bagi mahasiswa dalam mengembangkan wawasannya. Perkembangan teknologi saat ini menuntut generasi muda untuk menjadi generasi yang inovatif dan intelektual tinggi. Media cetak kini harus mengikuti arus zaman untuk mempertahankan eksistensi media tersebut, salah satunya dengan menjaga aktualitas tulisan. Di pondok pesantren Nurul Jadid Paiton Probolinggo – khususnya di Pusat Pendidikan Al-Qur'an Pondok Pesantren Nurul Jadid, media cetak merupakan media utama yang efisien dan efektif dalam menyebarluaskan informasi dan pengetahuan bagi pembaca. Dalam penelitian kualitatif deskriptif ini, peneliti menggunakan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi baik dari sumber offline maupun online. Berdasarkan analisis data yang terkumpul, dapat disimpulkan bahwa penggunaan media cetak berupa surat kabar di pondok pesantren dapat berdampak baik bagi pengembangan pengetahuan, produktivitas karya tulis, dan efektivitas penyebaran dakwah. Kata kunci: Efektivitas, Dakwah Bi al-Kitabah, Media Cetak